2008
DOI: 10.4067/s0717-97072008000400012
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Bis(2-Bromophenyl)disulfide Complexes

Abstract: The interactions of the new ligand bis(2-bromophenyl)disulfide (BrPh) 2 S 2 = L with transition metal ions are described. Octahedral complexes [ML 2 Cl 2 (H 2 O) 2 ] (M = Mn(II), Fe(II), Co(II) or Ni(II)) and [CrL 2 Cl 2 (H 2 O) 2 ]Cl were obtained and characterized by physicochemical and spectroscopic methods which suggest that the bis(2-bromophenyl)disulfide behaves as a monodentate ligand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The modest effect of the C56S mutation on inhibition in the Mg 2+ compared to the Mn 2+ context also suggests a differential chelation effect in the active site. Although we did not find significant complexation between DIBA-1 and Mn 2+ prior to IN binding under our experimental conditions, it is not excluded that such a complexation may occur with Mn 2+ , but not with Mg 2+ , in the active site context for proximity reasons, based on a recent study on complexes involving bis(2-bromophenyl)disulfide and transition metals ( 39 ). However, DIBA-1 was clearly and reproducibly a better inhibitor in the context of Mg 2+ than Mn 2+ , suggesting that the differential effect originates mainly in the zinc ejection which can be considered as the most potent inhibition mechanism.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The modest effect of the C56S mutation on inhibition in the Mg 2+ compared to the Mn 2+ context also suggests a differential chelation effect in the active site. Although we did not find significant complexation between DIBA-1 and Mn 2+ prior to IN binding under our experimental conditions, it is not excluded that such a complexation may occur with Mn 2+ , but not with Mg 2+ , in the active site context for proximity reasons, based on a recent study on complexes involving bis(2-bromophenyl)disulfide and transition metals ( 39 ). However, DIBA-1 was clearly and reproducibly a better inhibitor in the context of Mg 2+ than Mn 2+ , suggesting that the differential effect originates mainly in the zinc ejection which can be considered as the most potent inhibition mechanism.…”
Section: Discussioncontrasting
confidence: 60%
“…Indeed, adding DTT or β-mercaptoethanol to the reaction mixture blocked the DIBA-1 inhibitory effect ( Figure 2 E). Recently, it has been reported that complexation reactions between bis(2-bromophenyl)disulfide and transition metal ions, including manganese, may occur ( 39 ). To address the question of the possible complexation between DIBA-1 and Mn 2+ —which could explain the higher IC 50 values obtained in the presence of Mn 2+ compared to Mg 2+ —we tested the influence of the order of addition of the reagents on the IC 50 value.…”
Section: Resultsmentioning
confidence: 99%
“…Changes observed in the weak absorption bands at 400-600 cm À1 in the spectra of the complexes were assigned to the M-O stretching vibrations [42,43]. The IR spectra of the phen-containing complexes 4d, 4f and 4g were similar to each other and showed new absorption bands characteristic of chelating phenanthroline [44], these occurring at ca.…”
Section: Ir Spectramentioning
confidence: 88%
“…In contrast to the reactions of Pd­(OAc) 2 with the dichalcogenides {HL Y } 2 , the corresponding reactions of nickel­(II) acetate with the dichalcogenides did not result in cleavage of the Se–Se or Te–Te bonds. This is not completely surprising because the analogous disulfide {HL S } 2 forms monomeric complexes of the type [Ni­{κ 5 -L S } 2 (solvent)] or dimeric complexes of the type [(Ni­{κ 5 -L S } 2 ) 2 ], where the disulfide moiety coordinates but remains intact. , Similarly, other disulfides have been observed to coordinate through one of the disulfide sulfur atoms to nickel. Only one example of a ditelluride coordinating to nickel has been claimed but was not proven unambiguously, e.g., by X-ray diffraction…”
Section: Resultsmentioning
confidence: 99%